2015
DOI: 10.1037/adb0000082
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal substance exposure: What predicts behavioral resilience by early adolescence?

Abstract: Understanding behavioral resilience among at-risk adolescents may guide public policy decisions and future programs. We examined factors predicting behavioral resilience following intrauterine substance exposure (IUSE) in a prospective longitudinal birth-cohort study of 136 early adolescents (age 12.4–15.9) at-risk for poor behavioral outcomes. We defined behavioral resilience as a composite measure of lack of early substance use initiation (before age 14), lack of risky sexual behavior, or lack of delinquency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
1
6
1
1
Order By: Relevance
“…However, the frequent co‐occurrence of prenatal and postnatal exposures (Astley, ; Astley et al, ; Gibbard, ; Hyter, ; Koponena et al, ) suggests that models should incorporate both time periods. In addition to the small number of studies that have examined interactions between PAE and other prenatal exposures (Price et al, ), a few studies outside the PAE literature have examined the combined effects of prenatal cocaine exposure and postnatal adversity on development (Eiden, Coles, Schuetze, & Colder, ; Eiden, Godleski, Colder, & Schuetze, ; Eiden, Granger, Schuetze, & Veira, ; Liebschutz et al, ) or the differential impacts of stress during prenatal and postnatal periods (Jensen et al, ; Jensen et al, ). Together, this literature highlights the importance of incorporating information from both prenatal and postnatal periods into the assessment of individual exposure profiles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequent co‐occurrence of prenatal and postnatal exposures (Astley, ; Astley et al, ; Gibbard, ; Hyter, ; Koponena et al, ) suggests that models should incorporate both time periods. In addition to the small number of studies that have examined interactions between PAE and other prenatal exposures (Price et al, ), a few studies outside the PAE literature have examined the combined effects of prenatal cocaine exposure and postnatal adversity on development (Eiden, Coles, Schuetze, & Colder, ; Eiden, Godleski, Colder, & Schuetze, ; Eiden, Granger, Schuetze, & Veira, ; Liebschutz et al, ) or the differential impacts of stress during prenatal and postnatal periods (Jensen et al, ; Jensen et al, ). Together, this literature highlights the importance of incorporating information from both prenatal and postnatal periods into the assessment of individual exposure profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The review includes 4 articles that focus on the prevalence of prenatal exposure to cannabis [3,5,6,45], 7 articles that discuss detection methods for the use of drugs in pregnant women [7][8][9][10][11][12]46], 9 molecular studies [13][14][15][16][17][18][19][20]47], 6 studies on rodents [21][22][23][24][25]48] and 33 articles on the relationship between cannabis exposure and developmental/psychopathological consequences [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][49][50][51][52][53]…”
Section: Methodsmentioning
confidence: 99%
“…For example, a survey of 19 303 middle to high school students from 82 Norwegian schools found that specific factors, such as the quality of parent–child relationships and absence of negative drug‐related beliefs, close relationships with drug users, low delinquency rates, regular tobacco use and alcohol intoxication, predicted resilience to teenage cannabis use . Behavioural resilience, defined as the lack of early (<14 years) substance use, risky sexual behaviour or delinquency, is also positively influenced by strict caregiver supervision, lower violence exposure and absence of intra‐uterine tobacco exposure even in children exposed to prenatal drugs, such as cocaine . There is ample evidence to show that programmes designed to enhance and support individual and family resilience have lasting effects, not only on drug use but also on suicidal risk, depression, anxiety, disruptive behaviours and even intergenerational vulnerability to such adversities …”
Section: Emotional Behavioural and Social Adjustmentmentioning
confidence: 99%
“…55 Behavioural resilience, defined as the lack of early (<14 years) substance use, risky sexual behaviour or delinquency, is also positively influenced by strict caregiver supervision, lower violence exposure and absence of intra-uterine tobacco exposure even in children exposed to prenatal drugs, such as cocaine. 56 There is ample evidence to show that programmes designed to enhance and support individual and family resilience have lasting effects, not only on drug use 57 but also on suicidal risk, 58 depression, anxiety, disruptive behaviours 58 and even intergenerational vulnerability to such adversities. 59…”
Section: Drug-exposed Children As Adultsmentioning
confidence: 99%